The Effect of Knowledge Management Implementation and Motivation on Employee Performance with Learning Organization as an Intervening Variable (Study on a Construction Consulting Service Company INKINDO East Java Member) - Ibnul Watoni (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to determine the Influence of Application Knowledge Management And Motivation To Employee Performance that is mediated by Learning Organization either directly or indirectly. The data in this study using the data tabulation of respondents from the results of the questionnaire. The sample used in this research is 248 employees in Construction Consultant Company of Inkindo Member of East Java. The analytical tool used is SEM (Structural Equation Modeling) analysis with Amos program. The primary data is obtained from the questionnaire which measurement using Likert scale which tested the validity and reliability, SEM evaluation and hypothesis test with the respondent's deskritif and variable. Result of research based on validity and reliability test show that data have valid and reliable. Based on the SEM test shows that Knowledge Management and Motivation affect the learning organization, besides Knowledge Management and motivation also have an effect on the performance that is mediated by learning organization either directly or indirectly.